A Novel access control model in cloud computing environment (PAR-AC) - Mahajan, Rini; Mahajan, Manish; Singh, Dheerendra (International Journal of Engineering and Technology, 2018)
Cloud computing has changed the perspective of information storage worldwide; still it has not fully matured. Security, privacy and access control of the stored data is the biggest concern in the IT industries and these are the major research areas in the field of cloud computing. Although many researchers have proposed variety of access control methods, still there is a scope of improvement. The main objective of this paper is to study the limitations of formerly proposed access control methods and to propose a better new access control method. It is the combination of Attribute based access control (ABAC), Hierarchical Role based access control (HRBAC) and Policy based authentica-tion. As a result we got a fine grained access control method. It also includes the feature of role delegation which is very important in pre-sent scenarios. Comparative analysis shows that proposed method combined many new features with existing access control methods to make the system sound.Â Â